Does the physical activity profile change in patients with hip dysplasia from before to 1 year after periacetabular osteotomy?. (2nd November 2018) - Jacobsen, Julie Sandell; Thorborg, Kristian; Hölmich, Per; Bolvig, Lars; Storgaard Jakobsen, Stig; Søballe, Kjeld; Mechlenburg, Inger
Abstract : Background and purpose — Knowledge of physical activity profiles among patients with hip dysplasia is lacking. We investigated whether patients with hip dysplasia change physical activity profile from before to 1 year after periacetabular osteotomy. Furthermore, we investigated associations between change in accelerometer-based physical activity and change in self-reported participation in preferred physical activities (PA). Patients and methods — Physical activity was objectively measured at very low to high intensity levels with accelerometer-based sensors. Subjectively, PA was recorded with Copenhagen Hip and Groin Outcome Score (HAGOS) in 77 patients. Associations between the 2 were analyzed with simple linear regression analyses. Results — Changes in accelerometer-based physical activity ranged from –2.2 to 4.0% points at all intensity levels from baseline to 1-year follow-up. These changes represent very small effect sizes (–0.16 to 0.14). In contrast, self-reported PA showed a statistically and clinically relevant increase of 22 (CI 14–29) HAGOS PA points 1 year post-surgery. Associations between change in accelerometer-based physical activity and change in self-reported PA were, however, not statistically significant and correspond to a percentage change in physical activity of only –0.87% to 0.65% for a change of 10 HAGOS PA points. Interpretation — Patients with hip dysplasia do not seem to change physical activity profile 1 year post-surgery if measured with objective accelerometer-based sensors. This is interesting as self-reported PA indicates that patients' ability to participate in physical activity increases, suggesting that this increased self-reported participatory capacity is not manifested as increased objectively measured physical activity.